Adrenomedullin: an important participant in neurological diseases - Feng-Jiao Li; Si-Ru Zheng; Dong-Mei Wang (Neural Regeneration Research, 2020)
Adrenomedullin, a peptide with multiple physiological functions in nervous system injury and disease, has aroused the interest of researchers. This review summarizes the role of adrenomedullin in neuropathological disorders, including pathological pain, brain injury and nerve regeneration, and their treatment. As a newly characterized pronociceptive mediator, adrenomedullin has been shown to act as an upstream factor in the transmission of noxious information for various types of pathological pain including acute and chronic inflammatory pain, cancer pain, neuropathic pain induced by spinal nerve injury and diabetic neuropathy. Initiation of glia-neuron signaling networks in the peripheral and central nervous system by adrenomedullin is involved in the formation and maintenance of morphine tolerance. Adrenomedullin has been shown to exert a facilitated or neuroprotective effect against brain injury including hemorrhagic or ischemic stroke and traumatic brain injury. Additionally, adrenomedullin can serve as a regulator to promote nerve regeneration in pathological conditions. Therefore, adrenomedullin is an important participant in nervous system diseases.